Evaluation of growth pacific white shrimp (Litopenaeus vannamei) in polyculture with red tilapia (Oreochromis mossambicus x O. niloticus) under a water recirculation system - Hernández-Barraza, César Arturo (Universidad Autónoma de Tamaulipas, 2011)
This study was conducted in the facilities of the Environmental Research Laboratory, University of Arizona for the purpose of evaluation by a preliminary study polyculture of the Pacific white shrimp (Litopenaeus vannamei) and Red Tilapia (Oreochromis mossambicus x O. niloticus). The experiment was conducted for 5 weeks using three groups of tilapia and shrimp three groups with four replicates. The various parameters evaluated in this study revealed the benefits that have both species polyculture, achieving good performance not only productive but also a high rate of survival. The shrimp were weighed and placed in baskets constructed with mosquito netting, which in turn were placed in plastic pools containing 300 liters of salty water to 5 ppm. Tilapia were randomly divided into three aquariums. Four fish weighing 40 g group in the first eight fish with 80 g in the second and twelve fish with 120 g in the third, respectively. The capacity of the tanks was 40 L each. These tanks were placed on wooden beams, over plastic wading pools fish and shrimp were fed a commercial diet containing 35% protein whereas 10% and 6% of their body weight respectively. The shrimp were weighed and randomly distributed in 5 individuals considering baskets/ basket. The data were evaluated using analysis of variance (ANOVA), considering the average weight gains of shrimp during their evaluation. The results showed significant difference (P < .05). Parameters such as oxygen, temperature, nitrate, nitrite, pH and salinity were maintained within the recommended ranges for growth of tilapia and shrimp The results showed that there was a significant difference (P < .05). The parameters such as oxygen, temperature, nitrate, nitrite, PH and salinity were maintained at adequate level for growing tilapia and pacific white shrimp.